THE TRANSPOSITION OF INTERNATIONAL CRIMINAL LAW CONCEPTS INTO NATIONAL JURISDICTIONS: THE CASE OF GENOCIDE - GIRARD, Marie-Hélène (Comparative Legilinguistics, 2019)
This article discusses preliminary findings of a study on the transposition of the legal concept of genocide into 131 national jurisdictions. The specificities of this transposition into national criminal systems, as well as those related to the international legal definition of genocide, are described in the first part. The communicative situations in which the concept of genocide has been transposed are then examined in order to show their scope and breadth, and to which extent they contribute to the transformation of the concept of genocide. Trends related to the object of transformation in the definition and their effect on meaning are subsequently outlined. The findings point to a situation where, despite having been the object of multiple consensus at the international level, the concept of genocide has been transformed by the vast array of domestic legal languages and legal systems into which it has been transposed and thereby reinforce the relation between the configuration of the language and law, and the difficulty of translation.